1995
DOI: 10.1016/0092-8674(95)90079-9
|View full text |Cite
|
Sign up to set email alerts
|

A targeting signal in VAMP regulating transport to synaptic vesicles

Abstract: VAMP is a synaptic vesicle membrane protein required for fusion. Synaptic vesicle targeting was measured for mutants of an epitope-tagged form of VAMP in transfected PC12 cells. A signal within a predicted amphipathic alpha helix is essential for targeting to synaptic vesicles. Cellubrevin, a nonneural VAMP homolog, contains this signal and is also targeted to synaptic vesicles. Amino acid substitutions within the synaptic vesicle targeting signal either enhance or inhibit sorting of VAMP to synaptic vesicles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
217
3
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(234 citation statements)
references
References 34 publications
12
217
3
2
Order By: Relevance
“…Collectively these data suggest a key role for substrate residues Nterminal to the cleavage site as determinants of the specificity of BoNT/B. This region of VAMP has also been identified as a conserved signal sequence which plays a role in the regulation of VAMP transport to synaptic vesicles [18,19].…”
Section: Discussionmentioning
confidence: 86%
“…Collectively these data suggest a key role for substrate residues Nterminal to the cleavage site as determinants of the specificity of BoNT/B. This region of VAMP has also been identified as a conserved signal sequence which plays a role in the regulation of VAMP transport to synaptic vesicles [18,19].…”
Section: Discussionmentioning
confidence: 86%
“…In other studies, we have observed significant differences between the role of targeting signals in PC12 cells and in our in vivo assays. Specifically, we examined the role of previously defined SV targeting signals of synaptobrevin (Grote et al, 1995). We introduced into the C. elegans synaptobrevin gene two specific lesions (M46A and N49A), which altered targeting of synaptobrevin in PC12 cells.…”
Section: Caenorhabditis Elegans As a Model System To Study Protein Tamentioning
confidence: 99%
“…In keeping with this idea multiple signal sequences have been found within the cytoplasmic domain of synaptobrevin and synaptotagmin. In neuroendocrine PC12 cells, a sorting signal of synaptobrevin consisting of residues 41-50 probably functions at the plasma membrane because its deletion prevented endocytosis and SLMV targeting (Grote et al, 1995;Grote and Kelly, 1996). In contrast, residues 31-38 of synaptobrevin are required at a sorting stage other than endocytosis at the plasma membrane because a deletion mutant lacking these amino acids was endocytosed normally but excluded from SLMV (Grote et al, 1995).…”
Section: Synaptic Localization Signals In Other Systemsmentioning
confidence: 99%
See 2 more Smart Citations